To play is necessary - Angela Vargas; Lúcia Schmitt (Universidade Federal de Santa Catarina, 2008)
This work tries to contemplate on playing, leaving of the observations on the children's games accomplished during the apprenticeship and the articulation of those with some theoretical ones that have been dedicating if to the study of the game, of the childhood and of the Infantile Education. It was possible, through the apprenticeship registrations and of the observations to live many moments in that the two groups, 3A and 3B, they played incorporating objects and creating characters in your games. He/she gave way, we sought focar the game of the do-of-bill, contemplating on your importance for the children in the first childhood, and that possibilities she brings us in the amplification of the infantile experiences. Another important aspect in this article is to contemplate on the teacher's practice in the Infantile Education, and, through our observations on playing of the children noticed the teachers' involvement in the children's games.